The SPACE of Developer Productivity. - FORSGREN, NICOLE; STOREY, MARGARET-ANNE; MADDILA, CHANDRA; ZIMMERMANN, THOMAS; HOUCK, BRIAN; BUTLER, JENNA (Communications of the ACM, 2021)
The article examines computer software developer productivity, particularly focusing upon various misconceptions about productivity and the development of the multidimensional framework for site reliability engineers (SREs) known as SPACE. The article discusses the relationship between developer productivity and job satisfaction and well-being and how to utilize the SPACE framework.